Himenópteros parasitoides associados a cultivos orgânico e convencional de tabaco (nicotiana tabacum l.) em Santa Cruz do Sul, RS, Brasil - Dorfey, Cecília (2011)
The fauna of parasitic Hymenoptera is not well known in Brazil, despite its great diversity and biological, ecological and economical importance. In the cultivation of tobacco (Nicotiana tabacum L.) there is the need to inventory the species of natural enemies that occur associated and perform the natural biological control of pests. The objectives of this study were to inventory the biodiversity of parasitic Hymenoptera associated with tobacco under conventional and organic management; to examine the seasonal and spatial distribution; and to check the effect of the presence of adjacent vegetation on populations of parasitoids. The study was conducted in two crops of conventional tobacco and one certified as organic in Santa Cruz do Sul, RS, Brazil. Sampling points were determined and located Outside , at the Border , Inside and in the Middle of the tobacco fields, in which were installed a Malaise trap and four pit-fall traps. Samples were weekly collected from November 2008 to February 2009 and from November 2009 to February 2010. Statistical analysis was performed using the software PAST. Were collected 7.913 hymenopterans parasitoids in conventional tobacco crops during the 2008/2009 and 2009/2010 crop, and 31.574 hymenopterans parasitoids associated with organic tobacco in both seasons of study. The families Ichneumonidae, Braconidae, Scelionidae and Eucoilidae were the most abundant in both types of crop management, as well as Encyrtidae, Eulophidae and Mymaridae. The sampling point "Outside" was the most representative in both crops, reflecting, in general, the need to maintain areas of adjacent vegetation that differ from the main crop in order to contribute to hymenopterans parasitoids associated with tobacco cultivation. However, application of agrochemicals reflected in the decrease of parasitoids sampled, underscoring the need for studies on selectivity of products currently used to control pests in tobacco on beneficial insects.